ประสบการณ์ข้ามวัฒนธรรมของนักเรียนพยาบาลทหารอากาศและนักเรียนพยาบาลเหล่าทัพ: โครงการแลกเปลี่ยนของวิทยาลัยพยาบาลทหารอากาศและโรงเรียนพยาบาลเหล่าทัพ สาธารณรัฐเกาหลี - เปาโรหิตย์ วัชราภรณ์ (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2015)
โครงการแลกเปลี่ยนวิทยาลัยพยาบาลทหารอากาศและโรงเรียนพยาบาลเหล่าทัพสาธารณรัฐเกาหลีได้ดำเนินมาตั้งแต่ พ.ศ. 2555 จนถึงปัจจุบัน โดยมีวัตถุประสงค์เพื่อแลกเปลี่ยนประสบการณ์การเรียนรู้และการฝึกเพื่อให้การพยาบาลในภาวะจลาจลและฉุกเฉิน โปรแกรมการฝึก 5 วัน ในปี 2557 การฝึกเน้นการฝึกในสถานการณ์จำลองอุบัติภัยทางธรรมชาติและการพยาบาลในสนามรบ วัตถุประสงค์ของการศึกษาเพื่อ 1) อธิบายวิธีการฝึกในสถานการณ์ภัยพิบัติ ภาวะอุบัติเหตุและฉุกเฉิน 2) อธิบายความแตกต่างทางวัฒนธรรมด้านการปกครองบังคับบัญชาของนักเรียนพยาบาลทหารอากาศและนักเรียนพยาบาลเหล่าทัพ และ 3) ศึกษาอุปกรณ์ที่ใช้เพื่อการฝึกทักษะ การวิจัยนี้เป็น การวิจัยเชิงคุณภาพ ตัวอย่าง เลือกแบบเจาะจงจาก นักเรียนพยาบาลทหารอากาศ 10 คน และนักเรียนพยาบาลเหล่าทัพ 10 คน การวิเคราะห์ข้อมูลใช้ Content Analysis ผลการวิจัย พบว่า 1) วิธีการฝึกในสถานการณ์ภัยพิบัติ ภาวะอุบัติเหตุและฉุกเฉิน ของวิทยาลัยพยาบาลเหล่าทัพคือการฝึกเสมือนเหตุการณ์จริง ส่วนการฝึกของวิทยาลัยพยาบาลทหารอากาศคือการฝึกที่มีความเป็นพยาบาลทหารเหมือนกันกับโรงเรียนพยาบาลเหล่าทัพ ซึ่งฝึกโดยผู้เชี่ยวชาญ ฝึกคัดแยกผู้บาดเจ็บฝึกสถานการณ์จำลองกรณีแผ่นดินไหว การพยาบาลในสนามรบและการพยาบาลฉุกเฉิน 2) ความแตกต่างทางวัฒนธรรมในระบบการปกครองบังคับบัญชา ของวิทยาลัยพยาบาลเหล่าทัพคือ นักเรียนอาวุโสกว่าฝึกหนักกว่า ส่วนของวิทยาลัยพยาบาลทหารอากาศคือ ความรักและการเคารพ สิ่งที่เหมือนกันคือ ความรู้สึก ภาคภูมิใจและศักดิ์ศรีของนักเรียนทั้งสองสถาบัน การสื่อสารไม่เป็นอุปสรรคเพราะมีการเตรียมการอย่างดีและ 3) อุปกรณ์การฝึกเพื่อพัฒนาทักษะทางด้านการพยาบาลทหารของวิทยาลัยพยาบาลเหล่าทัพคือความทันสมัยและความสลับซับซ้อน ส่วนของวิทยาลัยพยาบาลทหารอากาศคือการฝึกที่เน้นวัตถุประสงค์เฉพาะด้าน ข้อเสนอแนะ โครงการแลกเปลี่ยนของวิทยาลัยพยาบาลทหารอากาศและโรงเรียนพยาบาลเหล่าทัพสาธารณรัฐเกาหลีเป็นโครงการที่มีความเป็นเอกลักษณ์ นักเรียนพยาบาลทหารอากาศและนักเรียนพยาบาลเหล่าทัพได้เรียนรู้ประสบการณ์ข้ามวัฒนธรรมที่เป็นประโยชน์และสามารถนำมาประยุกต์ใช้เมื่อต้องปฏิบัติงานกับพยาบาลต่างชาติ ผู้บริหารสถาบันจึงควรสนับสนุนให้โครงการนี้ดำเนินการอย่างต่อเนื่อง Air Force Student Nurses and Cadets’ Cross-Cultural Experiences: The Exchange Program of Royal Thai Air Force Nursing College and Korea Armed Forces Nursing Academy, 2014. ABSTRACT Exchange Program of Royal Thai Air Force Nursing College (RTAFNC) and Korea Armed Forces Nursing Academy (KAFNA) began in 2012. The program launches continuously every year. The main purpose of the program is to exchange learning experiences of how to train to be a good military nurse in insurgent and calamity circumstance. The program was 5 days training which focused on disaster and emergency nursing and cultural tour. In 2014, the exchange program emphasized on simulation of natural disaster and in the battle field which could be applied to the RTAFNC context both in theory and practice. The objectives were 1) to explain how to train when encounter disaster and emergency nursing, 2) to describe cultural differences of the Thai Air Force student nurses and KAFNA cadets, and 3) to identify training material for skill development. Qualitative study was done. Research instrument were interview and journal writing. Content analysis was used to discover significant concepts. Ten Air Force student nurses, RTAFNC and ten cadets, KAFNA were purposively selected for the samples. The findings were as follows: 1) The strategy of training was defined as “Training as Fighting” and “Doing the Same”. Theories of disaster and emergency nursing were taught by expert professors. Table exercise was done to develop triage competency. Simulation of earth quake was used to train disaster nursing and simulation of wartime was used to train for emergency nursing. 2) Cultural differences in term of command and control system defined as “Seniors do Harder than Juniors”. and “Love and Respect” Seniors did physical exercises harder than junior cadets where as senior AFSNs did physical exercises less than junior AFSNs. The sense of pride and discipline of cadets and AFSN were found the same. Communication is not a barrier since they were well prepared. 3) Training materials for skill development defined as “Complicated and Modernized” and “ Specific Purpose”. Training materials of KAFNA were complicated and modernized whereas RTAFNC had less training materials but for a specific purpose of training. Exchange Program of RTAFNC and KAFNA was a unique program. Cadets and AFSN were satisfied with the program because they gained precious experiences of military training and cultural differences. This program should be continued and supported by the leaders of the two institutions.